Privatporträt. Die Darstellung realer Personen in der spätantiken und byzantinischen Kunst: Akten des Internationalen Workshops an der Österreichischen Akademie der Wissenschaften in Wien 14.-15. Februar 2013 (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
Research on occasions and forms of private representation in art from the close of Antiquity to the end of the Middle Ages has so far been carried out rarely and not very systematically. This volume presents the proceedings of an international conference held at the Austrian Academy of Sciences in 2013. His contributions were devoted to private portraits between Late Antiquity and Byzantium on very different groups of monuments and on aspects in a broad diachronic and methodological perspective.